The substantia nigra and ventral tegmental dopaminergic neurons: from development to neurodegeneration - Fu, Y.; Paxinos, G.; Watson, Charles; Halliday, G. (2016)
The pathology of Parkinson’s disease (PD) is characterised by the loss of neurons in the substantia nigra parcompacta (A9), which results in the insufficient release of dopamine, and the appearance of motor symptoms. Not all neurons in the A9 subregions degenerate in PD, and the dopaminergic (DA) neurons located in the neighboring ventral tegmental area (A10) are relatively resistant to PD pathogenesis. An increasing number of quantitative studies using human tissue samples of these brain regions have revealed important biological differences. In this review, we first describe current knowledge on the multi-segmental neuromere origin of these DA neurons. We then compare the continued transcription factor and protein expression profile and morphological differences distinguishing subregions within the A9 substantia nigra, and between A9 and A10 DA neurons. We conclude that the expression of three types of factors and proteins contributes to the diversity observed in these DA neurons and potentially to their differential vulnerability to PD. In particular, the specific axonal structure of A9 neurons and the way A9 neurons maintain their DA usage makes them easily exposed to energy deficits, calcium overload and oxidative stress, all contributing to their decreased survival in PD. We highlight knowledge gaps in our understanding of the cellular biomarkers for and their different functions in DA neurons, knowledge which may assist to identify underpinning disease mechansims that could be targeted for the treatment of any subregional dysfunction and loss of these DA neurons.